THE NECESSITY AND TRUST OF CITIZENS OF BOGOR TO SHARIA MICROFINANCE INSTITUTION - Alhifni, Anas; Mukhlish, Zaini; Ahwarumi, Biyati; Hasib, Fatin Fadhilah (Program Studi Ekonomi Islam FEI UNIDA Bogor, 2019)
The interest of the public to put their money in the financial sanctuary is an important thing to note, especially for sharia microfinance institutions that are generally still less desirable public. The objective of this research is to analyze the needs, expectation, challenge, and belief of the community toward SMI in Bogor city. The method used in this research is the Structural Equation Modeling (SEM AMOS 22) population of Bogor city community with 200 samples. The results of data analysis show that the community simultaneously has the needs, expectations, challenges, and beliefs of SMI. As with the statistical necessity with expectations, challenges with beliefs and expectations with trust have significant relationships and only variable needs with challenges that have no real relationship because of the value of both above the value that is 0.506â‰¥0.05.